2022
DOI: 10.3390/plants11121593
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Composition Analysis of Maize Hybrids Affected by Different Nitrogen Fertilisation Systems

Abstract: Maize is one of the most widely used plants in the agricultural industry, and the fields of application of this plant are broad. The experiment was conducted at the Látókép Crop Production Experimental Station of the University of Debrecen, Hungary. Three mid-ripening maize hybrids with different FAO numbers were used in the present study. The effects of different nitrogen supplies were examined as a variable rate of abiotic stress and the interrelationship among the essential nutrients through the nutrient ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
1
13
2
Order By: Relevance
“…A previous study by Krismawati et al (2021) found a strong positive correlation between plant height, number of seeds per cob, seed weight and dry weight of corn due to the application of biochar and inorganic fertilizers. This is supported by Bojtor et al (2022), reporting that the formation of corn is influenced by elements of N, P and K because nitrogen plays a role in photosynthesis, K functions in stem tissue to strengthen stems and leaf formation, while phosphorus contributes to the formation of corn grains, leaves, stems and cobs. The results did not show a correlation between soil and plant parameters, this is presumably because soil parameters, such as physical properties, are more influenced by organic matter, while plant parameters are more affected by the dose of inorganic fertilizer given.…”
Section: Correlation Of Observation Variablesmentioning
confidence: 75%
“…A previous study by Krismawati et al (2021) found a strong positive correlation between plant height, number of seeds per cob, seed weight and dry weight of corn due to the application of biochar and inorganic fertilizers. This is supported by Bojtor et al (2022), reporting that the formation of corn is influenced by elements of N, P and K because nitrogen plays a role in photosynthesis, K functions in stem tissue to strengthen stems and leaf formation, while phosphorus contributes to the formation of corn grains, leaves, stems and cobs. The results did not show a correlation between soil and plant parameters, this is presumably because soil parameters, such as physical properties, are more influenced by organic matter, while plant parameters are more affected by the dose of inorganic fertilizer given.…”
Section: Correlation Of Observation Variablesmentioning
confidence: 75%
“…For the proper growth of plants, seventeen elements are required (i.e., C, H, O, N, P, K, Ca, Mg, S, Fe, Zn, Mn, B, Cu, Mo, Cl, Ni) [ 92 , 93 ]. The carbon, hydrogen, and oxygen are uptaken from carbon dioxide and water, while the remaining elements, termed mineral nutrients, are from the soil [ 92 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving food self-sufficiency in Africa requires that N usage increase from 35 kg/ha to 181 kg/ha per year during 2016-2050, although this will be associated with high N losses and low nitrogen use efficiency (57). In maize production, for instance, N application at 120 kg ha -1 is found optimal for yields in SSA, and beyond this application, the N is stored in the leaves and stems, making it very useful for animal fodder (58). However, considering the diversity in the soil types, the optimal rate may vary while Elrys et al (57) admitted that considering several constraints facing the African fertilizer sector, it is impossible to attain the 181 kg N/ha per year application.…”
Section: Macronutrient (Npk) Requirements To Increase Food Production...mentioning
confidence: 99%